(untitled) (Prithvi Academic Journal, 2020)
This paper aims at assessing the need of book building pricing of IPOs as well as the level of agreement among market participants on its application in the context of Nepal. This study is based on a cross-sectional analysis of survey data of 71 respondents comprising 19 issue managers, 16 portfolio managers, six share registrars, 10 mutual funds, nine stock brokers and 11 retail investors, for the months of January and February 2020. Mainly, descriptive statistics and inferential statistics like one-way ANOVA have been used in the study to assess the need and level of agreement in adopting book building pricing. The study revealed that there is an urgent need of adopting book building mechanisms of IPO pricing in Nepal because the existing primary market is inefficient and there is a huge wealth loss of existing shareholders in terms of higher underpricing on equity offerings. The role of institutional investors followed by underwriters is found crucial especially to discover price band and final price i.e. cut-off price, of offerings under book building. Further, the level of agreement in adopting book building pricing in Nepal’s capital market is positive because (i) the price band is determined with the active support of qualified institutional investors, (ii) it lowers the degree of underpricing of IPOs than that of par value method, and (iii) book building help prevents „random free riders‟ from overwhelming the process of IPOs. Mainly, more active market participants, like issue managers, portfolio managers, and stockbrokers, have a high level of agreement in adopting book building pricing. The study findings associated with book building pricing are crucial and highly applicable in order to formulate policies and implementation of new pricing mechanism in Nepal. Implementation of book building pricing will contribute to reduce level of underpricing, attract real sector companies and/or foster the primary market efficiency in future.